Yuanzidan shi Meiguo fandongpai yonglai xiarende yizhi zhi laohu, kan yangzi kepa, shijishang bing bu kepa
'The atomic bomb is a paper tiger used by the American reactionaries to scare people, it looks scary but in fact it's not scary at all.'